Interannual variability of the earth’s spectral solar reflectance from measurements and simulations - Jin, Z.; Lukachin, C.; Roberts, Y.; Wielicki, B.; Feldman, D.; Collins, Bill (Wiley-Blackwell Publishing, 2014)
The mean solar spectral reflectance averaged over large spatiotemporal scales is an important climate benchmark data product proposed for the Climate Absolute Radiance and Refractivity Observatory mission. The interannual variability of these reflectances over the ocean is examined through satellite-measured hyperspectral data and through satellite instrument emulation based on model simulation. Such large domain-averaged reflectances show small interannual variation, usually under few percent, depending on the latitude region and spatiotemporal scale used for averaging. Although the interannual variation is usually less than the absolute accuracy ofmodel calculation, themodel simulated interannual variations are consistent with the measurements because most of the modeling errors in the reflectance averaged in large climate domains are systematic and are canceled out in the interannual difference spectra. The interannual variability is also shown to decrease as the temporal and spatial scales increase. Both the observational data and the model simulations show that the natural variability in the annualmean reflectance is about 50% lower than that in the monthly mean over all spectra. The interannual variability determined from observations in large climate domains also compares favorably with that from the climate Observing System Simulation Experiment based on climatemodel simulations; both show a standard deviation of less than 1% of the mean reflectance across all spectra for global and annual average over the ocean.